PROFIL DARAH IKAN NILA (Oreochromis niloticus) YANG DIBERI PAKAN DENGAN PENAMBAHAN EKSTRAK DAUN MANGROVE API-API PUTIH (Avicennia marina) - Iswardhani Ariyanti; Sri Marnani; Emyliana listiowati; Agung Cahyo Setiawan; Hamdan Syakuri; Muh. Sulaiman Dadiono (Jurnal Perikanan Pantura (JPP), 2022)
Medicinal plants can be used as alternative prevention and treatment of fish diseases. Its use can be mixed in the feed, but must be by the dose so as not to interfere with fish health. Fish health can be evaluated by measuring the blood profile. The blood profile of this study includes hemoglobin, hematocrit, blood glucose, and total erythrocytes. The purpose of this research was to determine the effect of adding Avicennia marina leaf extract as seen from the total erythrocytes, hemoglobin levels, hematocrit values, and blood glucose levels. The research method used was CRD consisting of 4 treatments and 5 individual replicates of tilapia. The addition of Avicennia marina extract to fish feed (1 g/kg; 1,5 g/kg; and 2 g/kg) had a total erythrocytes range of 0,995x106–2,658x106 cell/mm3, hemoglobin ranged from 8,3–11,6 g/dL, hematocrit ranged from 23.1–38,4 g/dL, and blood glucose ranged from 46–209 mg/dL. The results showed that the addition of Avicennia marina leaf extract had no significant effect (P>0,05) on the blood profile of fish as measured by total erythrocytes, hemoglobin, hematocrit​​, and glucose. Aquaculture water quality in the form of temperature and pH has the optimum value for tilapia cultivation.